Extracting entity-based information in cyber-physical systems - Yuchen Yang; Lijie Li; Guisheng Yin (International Journal of Distributed Sensor Networks)
This article proposes a framework P 3 E for evaluating entity extraction problem over cyber-physical system data. As known by us, this article is the first work focusing on this problem, which is an important step for identifying entities in cyber-physical system data. Directed by the initial entities, utilizing the relaxation and verification techniques, P 3 E provides a path expression–based solution for entity extraction problem, which has following characteristics. First, using path expressions, P 3 E provides a condensed presentation for entity locations whose size may get very large when scaling up the data size. Second, requiring only one entity example to indicate the interests, using relaxation technique, P 3 E can discover other similar entities automatically. Third, by adjusting the example given to P 3 E , users can specify their own interesting entities and control the entities discovered by P 3 E . Besides, utilizing the idea of sharing computations, by extending previous automaton techniques, an efficient implementation of P 3 E is provided. Experimental results are reported, which show that P 3 E can provide an effective and efficient solution to the entity extraction problem.